Cell-cell contact viral transfer contributes to HIV infection and persistence in astrocytes - Luo, Xiaoyu (J Neurovirol, 2014)
Astrocytes are the most abundant cells in the central nervous system and play important roles in HIV/neuroAIDS. Detection of HIV proviral DNA, RNA and early gene products but not late structural gene products in astrocytes in vivo and in vitro indicates that astrocytes are susceptible to HIV infection albeit in a restricted manner. We as well as others have shown that cell-free HIV is capable of entering CD4− astrocytes through human mannose receptor-mediated endocytosis. In this study, we took advantage of several newly developed fluorescence protein-based HIV reporter viruses and further characterized HIV interaction with astrocytes. First, we found that HIV was successfully transferred to astrocytes from HIV− infected CD4+ T cells in a cell-cell contact- and gp120-dependent manner. In addition, we demonstrated that compared to endocytosis-mediated cell-free HIV entry and subsequent degradation of endocytosed virions, the cell-cell contact between astrocytes and HIV-infected CD4+ T cells led to robust HIV infection of astrocytes but retained the restricted nature of viral gene expression. Furthermore, we showed that HIV latency was established in astrocytes. Lastly, we demonstrated that infectious progeny HIV was readily recovered from HIV latent astrocytes in a cell-cell contact-mediated manner. Taken together, our studies point to the importance of the cell-cell contact-mediated HIV interaction with astrocytes and provide direct evidence to support the notion that astrocytes are HIV latent reservoirs in the central nervous system.